Neutrosophic D’Agostino Test of Normality: An Application to Water Data - Mohammed Albassam; Nasrullah Khan; Muhammad Aslam (Journal of Mathematics)
The D’Agostino test has been widely applied for testing the normality of the data. The existing D’Agostino test cannot be applied when the data have some indeterminate observations or observations which are obtained from the complex systems. In this paper, we present a D’Agostino test under neutrosophic statistics. We propose the D’Agostino test to test the normality of the data having indeterminate observations. The design of the proposed test is given and implemented with the help of real data. From the comparison, it is concluded that the proposed test is effective, adequate, and suitable to be applied in the presence of indeterminacy.